2015
DOI: 10.20452/pamw.3117
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in patients after surgical and transcatheter aortic valve replacement

Abstract: INTRODUCTION Transcatheter aortic valve implantation (TAVI) and minimally invasive aortic valve replacement (minithoracotomy and ministernotomy) have become a valuable alternative to conventional surgical treatment of severe aortic stenosis (AS) in high-risk patients. OBJECTIVESThe aim of the study was to evaluate long-term results and complications in patients with symptomatic AS treated with TAVI, surgical aortic valve replacement (SAVR), minithoracotomy, or ministernotomy. PATIENTS AND METHODSA total of 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…Complete clinical results and follow‐up data were reported previously . Briefly, TAVI group consisted of 39 patients (22.5%), mini‐sternotomy was performed in 44 patients (25.5%), mini‐thoracotomy in 50 (29%), and AVR in 40 patients (23%).…”
Section: Resultsmentioning
confidence: 84%
“…Complete clinical results and follow‐up data were reported previously . Briefly, TAVI group consisted of 39 patients (22.5%), mini‐sternotomy was performed in 44 patients (25.5%), mini‐thoracotomy in 50 (29%), and AVR in 40 patients (23%).…”
Section: Resultsmentioning
confidence: 84%
“…12) Previous data showed that there were no significant differences between TAVI patients and patients undergoing AVR via minithoracotomy, ministernotomy, and surgical AVR in terms of blood transfusions during hospitalization, however, access site complications were frequent. 30) Limitations: Our findings are presented with several limitations including a small sample size and recruitment from only one center. The overall number of deaths at 12 months was low (18 events) and thus the results from multivariate Cox regression analysis should be considered to be rather exploratory and hypothesis-generating.…”
Section: Discussionmentioning
confidence: 94%
“…Despite their detrimental effects on general health status, overweight and obesity were linked with a protective effect in a wide range of cardiovascular interventions [2][3][4][5]. This discrepancy was also reported in patients with severe aortic stenosis (AS) undergoing transcatheter aortic valve implantation (TAVI) [3,[6][7][8][9][10][11][12]. However, some studies reported no effect of body mass index (BMI) on outcomes in patients undergoing TAVI [13,14].…”
Section: Introductionmentioning
confidence: 99%